2019
DOI: 10.2175/106143017x15131012188024
|View full text |Cite
|
Sign up to set email alerts
|

Understanding urban stormwater denitrification in bioretention internal water storage zones

Abstract: Conventional free-draining bioretention systems promote nitrate production and continual 23 leaching to receiving waters. In this study, laboratory tests demonstrated the efficacy of an 24 internal water storage zone (IWSZ) to target nitrate removal via denitrification. Experimental 25 results confirmed that the carbon substrate characteristics (Willow Oak woodchip media) and the 26 hydraulic retention time of nitrified stormwater affected nitrate removal performance. A 2.6-day 27 batch treatment time reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…A larger thickness is not expected to improve ammonification. The DON ammonification/adsorption layer in a bioretention system can be placed immediately below the first top mixed layer of sand and plant–soil (rhizosphere zone). The generated ammonium can be subsequently removed through adsorption and nitrification/denitrification processes in bioretention lower layers (Ergas et al, 2010; Igielski et al, 2019; Khorsha & Davis, 2017a, 2017b; Peterson et al, 2015). The total bioretention depth could still remain at 1.2 m or somewhat deeper to include media layers to address all N species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger thickness is not expected to improve ammonification. The DON ammonification/adsorption layer in a bioretention system can be placed immediately below the first top mixed layer of sand and plant–soil (rhizosphere zone). The generated ammonium can be subsequently removed through adsorption and nitrification/denitrification processes in bioretention lower layers (Ergas et al, 2010; Igielski et al, 2019; Khorsha & Davis, 2017a, 2017b; Peterson et al, 2015). The total bioretention depth could still remain at 1.2 m or somewhat deeper to include media layers to address all N species.…”
Section: Resultsmentioning
confidence: 99%
“…To remove nitrate/nitrite from stormwater, an Internal Water Storage (IWS) denitrification zone in bioretention cells is designed to remain saturated between storm events. In this zone, anoxic conditions could be developed to encourage denitrification, Equation ( 4) (e.g., Ergas et al, 2010;Igielski et al, 2019;Peterson et al, 2015;Zinger et al, 2013). Mohtadi et al (2017) have found that several model stormwater organic nitrogenous compounds may not appreciably be removed from stormwater through adsorption process; for instance, the highest adsorption capacity for urea on several examined adsorbents, for example, coal activated carbon (AC), coconut-shell AC, and quartz sand, was less than 0.04 mg N/g.…”
Section: Introductionmentioning
confidence: 99%
“…The stored water, which is not exposed to the air and thus is not aerated, will become anaerobic and can support the bacterial population needed for denitrification. For example, Igielski et al (2019) investigated rain gardens with an internal water storage zone and found nitrate was reduced from 3.0 mg N/L to less than 0.01 mg N/L with a hydraulic residence time of 2.6 days. Qiu et al (2019) used an internal water storage zone in a bioretention practice that also contained WTRs as an enhancing agent for phosphorus removal.…”
Section: Rain Gardens For Nitrogen Removalmentioning
confidence: 99%
“…Four-year demonstration of a bioretention system modified with an internal water storage zone (Igielski, Kjellerup, & Davis, 2019) achieved effluent total N concentrations of <0.75 mg N L −1 and removed 81% of NO x (NO 3 − + NO 2 − ) (Lopez-Ponnada, Lynn, Ergas, . Testing of an 11-yr-old bioretention cell suggested that P and metals will not accumulate to levels requiring media replacement for the design life of associated development the cell serves (Johnson & Hunt, 2016).…”
Section: Stormwater Treatmentmentioning
confidence: 99%